Belonging and Narrative A Theory of the American Novel (Edition 1) - Bieger, Laura (transcript Verlag, 2018)
Why did the novel become so popular in the past three centuries, and how did the American novel contribute to this trend? As a key provider of the narrative frames and formulas needed by modern individuals to give meaning and mooring to their lives. Drawing on phenomenological hermeneutics, human geography and social psychology, Laura Bieger contends that belonging is not a given; it is continuously produced by narrative. Against the current emphasis on metaphors of movement and destabilization, she explores the salience and significance of home. Challenging views of narrative as a mechanism of ideology, she approaches narrative as a practical component of dwelling in the world - and the novel a primary place-making agent.